2010
DOI: 10.1007/s12199-010-0193-7
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively active Stat5A and Stat5B promote adipogenesis

Abstract: Objective The metabolic syndrome is an important social problem affecting many people in developed countries. Obesity is a leading cause of this syndrome, hence understanding molecular mechanisms underlying obesity is of prime importance for preventive medicine to develop novel methods to alleviate the corresponding social cost as well as for pharmaceutical companies to develop antimetabolic drugs. Methods Since adipocytes play an important role in obesity, we explored the signaling pathways leading to differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…A recent study suggested that the nuclear peroxisome proliferator-activated receptor γ (PPARγ) could activate CHK2 in the development of follicular thyroid cancer [24]. In addition, PPARγ transcription has been shown to be regulated by STAT-5 in adipogenesis [25]. We therefore investigated if the expression of PPARγ was altered by STAT-5 in HPV31-positive CIN612 cells.…”
Section: Resultsmentioning
confidence: 97%
“…A recent study suggested that the nuclear peroxisome proliferator-activated receptor γ (PPARγ) could activate CHK2 in the development of follicular thyroid cancer [24]. In addition, PPARγ transcription has been shown to be regulated by STAT-5 in adipogenesis [25]. We therefore investigated if the expression of PPARγ was altered by STAT-5 in HPV31-positive CIN612 cells.…”
Section: Resultsmentioning
confidence: 97%
“…This is supported by data showing that STAT5 can directly bind and transactivate the PPARγ promoter [39,55,100]. Many transcription factors have profound effects on adipocyte development, but PPARγ is a critical transcriptional regulator that is absolutely required for fat cell differentiation [6,61].…”
Section: Regulation Of Adipogenesis By Stat Proteinsmentioning
confidence: 93%
“…Of the seven known STATs, only STAT3 and STAT5 are reported to positively affect adipogenesis. 3, 4, 5, 6, 7 Similarly, CREB has also been shown to enhance adipocyte differentiation. 8, 9, 10 Interestingly, although a dominant-negative CREB prevents induction of Cebpb during differentiation, a constitutive active CREB restores adipogenesis in cells with knockdown of C/EBP β , suggesting that CREB facilitates adipose conversion through others means than C/EBP β .…”
mentioning
confidence: 99%